IMPLEMENTASI MODEL INKUIRI TERBIMBING UNTUK MENINGKATKAN KEMAMPUAN BERFIKIR KRITIS SISWA PADA PEMBELAJARAN BIOLOGI KELAS X SMA N 9 PEKANBARU - Saputri, Emy; Syafi’i, Wan; Febrita, Elya (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Guided inquiry model is a learning model that involves students actively searching and finding concepts in learning activities with teacher direction. Active students in searching and finding concepts will make students critical thinking skills increase. The purpose of this study is to determine student’s critical thinking skills through the implementation of guided inquiry learning model on biology learning in class X MIA of state senior high school 9 Pekanbaru. The type of research conducted is quasi experimental research using pretest-posttest design. The study population all the students of class X, with a sample of class X MIA4 as an experimental class and class X MIA6 as a control class. In the learning process, the experimental class is the class given treatment by using guided inquiry learning model whiles the control class using conventional method. Data analysis techniques used are uji t and N-Gain. Based on hypothesis test result obtained tcount > ttable for animalia subject 1,84 > 1,72 and ecology 3,97>1,72 hypothesis accepted. Level of student’s understanding of animalia subject in the experimental class, value N-Gain 0,71 (high) and control class 0,61 (medium). Then the ecological subject in the experimental class of N-Gain value 0,73 (high) and the control class of N-gain value is 0,58 (medium). Based on the results of research shows that there are different of student’s critical thinking skills with and without using guided inquiry learning model in class X MIA state senior high school 9 Pekanbaru.Keywords: guided inquiry, critical thinking